2017
DOI: 10.1016/j.compositesa.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Digital image correlation as a strain measurement technique for fibre tensile tests

Abstract: A method is presented to test fibres in tension using direct strain measurement. This eliminates the need to test the fibres at multiple gauge lengths to correct for machine compliance, reducing the number of samples. Additionally, fibre slippage can contribute to the underestimation of the stiffness since this is not considered in the correction procedure. Steel fibres with a diameter of 30 µm, and a known stiffness of 193 GPa, were tested in tension using indirect methods and the direct strain method. Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 22 publications
0
41
1
Order By: Relevance
“…An overview of the mechanical properties found in literature of technical bamboo fibres is given in Table 1 of Depuydt et al. 38 Young’s moduli vary between 19 and 43 GPa and strength between 341 and 860 MPa. Different factors can be responsible for the large variation.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the mechanical properties found in literature of technical bamboo fibres is given in Table 1 of Depuydt et al. 38 Young’s moduli vary between 19 and 43 GPa and strength between 341 and 860 MPa. Different factors can be responsible for the large variation.…”
Section: Introductionmentioning
confidence: 99%
“…A digital camera with a spatial resolution of 96 dpi was used to record the speckle pattern applied to the sample. The distance between composite sample and camera was 1 m. During the test, subsequent images and force registration were taken with an interval of 150 ms[46]. Images were further analyzed with VIC-2D 2009 software to calculate the strain.…”
mentioning
confidence: 99%
“…In terms of stiffness, the addition of scutched flax enhanced both tensile and flexural moduli of PA6 significantly. The modulus increase is expected because the reported elastic modulus of flax is 45–60 GPa . However, the extent of stiffness enhancement is dictated by the processing methodology.…”
Section: Resultsmentioning
confidence: 99%
“…revealed that the lack of compounding kept the flax fibers in MIXsc mostly in their original, bundled technical fibers state. Based on previous studies that have reported slightly lower tensile modulus for technical fibers (~45 GPa) in reference to elementary fibers (60 GPa) , the E f quantity in Eq . is then an averaged technical/elementary fiber stiffness, which would be lower for MIXsc than SSSPsc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation